"A man knows a man": illustrating disability in Harper's Weekly after the Civil War. Issue 2 (4th May 2017) - Johnson, Russell L.
ABSTRACT: Images in the post-Civil War illustrated press regularly featured disability, manipulating it to make arguments which went beyond the obvious attempts to excoriate the South for attempting to dismember the Union and to acknowledge the sacrifices of the men who preserved it. These illustrations, however, have not received the attention they deserve, either in histories of the war's effects or in disability studies scholarship. To call attention to these over-looked sources, this essay explores the uses of disability in Harper's Weekly illustrations, focusing on depictions of Union army veterans with missing legs in the first two years after the war. These illustrations reflect complex attitudes towards disabled veterans after the war and offer a clear lesson in the ways disability is socially and culturally constructed as well as historically contingent.